2009
DOI: 10.1590/s1413-86702009000600008
|View full text |Cite
|
Sign up to set email alerts
|

Enteroparasitosis prevalence and parasitism influence in clinical outcomes of tuberculosis patients with or without HIV co-infection in a reference hospital in Rio de Janeiro (2000-2006)

Abstract: Tuberculosis and intestinal parasites affect primarily low social and economic level populations, living clustered in precarious habitational settings. One of the interesting aspects of this interaction is the parasitism influence in cellular response to tuberculosis. In the present study, we evaluated the prevalence of enteroparasitosis in tuberculosis patients, HIV-infected and non HIV infected, and we observed the influence of helminth presence in the response to tuberculin skin test (TST) and tuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 11 publications
6
30
4
1
Order By: Relevance
“…As for education and income, data agree with the social profile of the epidemic of Aids and TB, which in Brazil strike mainly the less economically favored classes of the population (3,(9)(10) . Even so, in the group of coinfected individuals, these indicators were even lower than the others.…”
Section: Discussionsupporting
confidence: 69%
“…As for education and income, data agree with the social profile of the epidemic of Aids and TB, which in Brazil strike mainly the less economically favored classes of the population (3,(9)(10) . Even so, in the group of coinfected individuals, these indicators were even lower than the others.…”
Section: Discussionsupporting
confidence: 69%
“…In contrast, coincident lymphatic filarial infection had no significant influence on tuberculin skin test positivity in a population endemic for Wuchereria bancrofti and hookworm infections and tuberculosis in South India [52]. Similar findings were seen in a study of patients in Brazil [53] and Peru [54], in which there was no difference in skin test reactivity between those with intestinal parasites and those without. A more recent study in South Africa similarly revealed no significant effect of antihelmintic treatment on tuberculin skin test or IGRAs in children [55].…”
Section: Helminth - Tuberculosis Co-infectionsupporting
confidence: 56%
“…Similarly, in Ethiopia, a significant association was observed between the incidence of TB disease and the presence of intestinal helminth infection [57]. However, in HIV positive populations in both Uganda and Brazil, neither gastrointestinal parasitic infections nor Mansonella perstans (a filarial nematode) was associated with progression to active TB, though in Uganda there was a relationship between having schistosomiasis and progression from LTBI to active TB [53, 58]. Interestingly, eosinophilia, that typically accompanies helminth infections, was found to be strongly associated with the risk of active TB in Africa [59].…”
Section: Helminth - Tuberculosis Co-infectionmentioning
confidence: 99%
“…The current limited evidence supports a potential immune modulating effect of helminths on mycobacterial immune responses in humans [15,21,23], although contradictory evidence also exists [24,25]. We therefore investigated the effect of an Ascaris- specific IgE positive status on a commonly used marker of M.tb infection (TST), in children in a setting with a high burden of tuberculosis.…”
Section: Introductionmentioning
confidence: 99%